High-dose melphalan and autologous stem cell transplantation as consolidation treatment in patients with chemosensitive ovarian cancer: Results of a single-institution randomized trial - Papadimitriou, C.; Dafni, U.; Anagnostopoulos, A.; Vlachos, G.; Voulgaris, Z.; Rodolakis, A.; Aravantinos, G.; Bamias, A.; Bozas, G.; Kiosses, E.; Gourgoulis, G.M.; Efstathiou, E.; et al. (Bone Marrow Transplantation, 2008)
The role of high-dose chemotherapy (HDCT) in epithelial ovarian cancer (EOC) remains controversial. This study was initiated to compare the efficacy and tolerability of HDCT as a consolidation approach in women with chemosensitive advanced EOC (FIGO stages IIC-IV). Patients who had achieved their first clinical complete remission after six cycles of conventional paclitaxel and carboplatin combination chemotherapy were randomly assigned to receive or not high-dose melphalan. The primary objective was to compare time to disease progression (TTP). A total of 80 patients were enrolled onto the trial. Patients who were randomized to receive HDCT were initially treated with cyclophosphamide 4g/m2 for PBPC mobilization. HDCT consisted of melphalan 200 mg/m2. Of the 37 patients who were allocated to HDCT, 11 (29.7%) did not receive melphalan either due to patient refusal (n = 5) or due to failure of PBPC mobilization (n = 6). In an intent-to-treat analysis, there were no significant differences between the two arms in TTP (P = 0.059) as well as in overall survival (OS) (P = 0.38).